Tool Kits in Regional Science Theory, Models, and Estimation - Sonis, Michael; Hewings, Geoffrey J. D. (Advances in Spatial Science, The Regional Science Series, 2009)
Regional Science is now more than 50 years old; in the last two decades, significant advances in methodology have occurred, spurred in large part by access to computers. The range of analytical techniques now available is enormous; this books provides a sampling of the toolkit that is now at the disposal of analysts interested in understanding and interpreting the complexity of the spatial structure of sub- national economies. The set of tools ranges from the more traditional (input-output) to new developments in computable general equilibrium models, nonlinear dynamics, neural modelling and innovation.